Views of rare disease participants in a UK whole-genome sequencing study towards secondary findings: a qualitative study - Mackley, M; Blair, E; Parker, M; Taylor, J; Watkins, H; Ormondroyd, E (Nature Publishing Group, 2018)
With large-scale genome sequencing initiatives underway, vast amounts of genomic data are being generated. Results—including secondary findings (SF)—are being returned, although policies around generation and management remain inconsistent. In order to inform relevant policy, it is essential that the views of stakeholders be considered—including participants who have made decisions about SF since the wider debate began. We conducted semi-structured interviews with sixteen rare disease patients and parents enrolled in genome sequencing to explore views towards SF. Informed by extensive contact with the healthcare system, interviewees demonstrated high levels of understanding of genetic testing and held pragmatic views: many are content not knowing SF. Interviewees expressed trust in the system and healthcare providers, as well as an appreciation of limited resources; acknowledging existing disease burden, many preferred to focus on their primary condition. Many demonstrated an expectation for recontact and assumed the possibility of later access to initially declined SF. In the absence of such an infrastructure, it is important that responsibilities for recontact are delineated, expectations are addressed, and the long-term impact of decisions is made clear during consent. Additionally, some interviewees demonstrated fluid views towards SF, and suggestions were made that perceptions may be influenced by family history. Further research into the changing desirability of SF and behavioural impact of disclosure are needed, and the development and introduction of mechanisms to respond to changes in patient views should be considered.